Análise empírica da reforma trabalhista brasileira de 2017 e seus reflexos sobre os indicadores do mercado de trabalho no período de 2015-2019 - Alves Júnior, Antônio Lisboa (2023)
This research focuses on the analysis of the Brazilian labor reform of 2017 and its impact on the labor market between 2015 and 2019. Questioning the effectiveness of the legislative changes in fostering positive impacts on labor market indicators, this study delves into the variation of indicators related to unemployment, underutilization, formal employment, and informality. The empirical analysis is based on secondary data from the Pesquisa Nacional por Amostra de Domicílios Contínua trimestral (PNAD Contínua) and utilizes the R programming language for analytical instrumentation. The main objective of this study is to examine the outcomes of the average rates of these indicators before and after the implementation of the reform. Specifically, it aims to assess the transformations brought about in the context of labor flexibility and deregulation, and to analyze the main structural changes caused by the labor reform. The underlying hypothesis of this research posits that, despite the proclaimed objectives of the labor reform, the legislative changes did not succeed in promoting substantial improvements in labor market indicators, and may have even deepened the precariousness of labor conditions. The findings of the investigation suggest that the reform was not effective in promoting employment expansion and reducing labor informality. The flexibility of labor relations promoted by the reform suggests a trend towards labor precarization, perpetuating or intensifying preexisting challenges in the labor market.